2013
DOI: 10.1007/s40565-013-0037-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential and policy issues for sustainable development of wind power in China

Abstract: This paper presents a macroscopic view on the prevailing policy and potential issues in respect of the sustainable wind power development in China. It starts by analyzing the characteristics of wind power resources and pin-pointing the relationship between the regulatory policies and various economic, taxation, legal and grid integration attributes relating to the wind power development. Then it follows by analyzing the status quo and capabilities of the wind power manufacturing industry in China including its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The charging coefficient of the part of subsystems can be increased, and the discharge coefficient can be reduced when partial subsystems must be preferentially filled according to the dispatch plan. Power distribution must be conducted on the basis of the initial values of SOC according to (1). Power must only be redistributed without SOC feedback control after the corresponding subsystem is full.…”
Section: Battery-charging Containermentioning
confidence: 99%
See 1 more Smart Citation
“…The charging coefficient of the part of subsystems can be increased, and the discharge coefficient can be reduced when partial subsystems must be preferentially filled according to the dispatch plan. Power distribution must be conducted on the basis of the initial values of SOC according to (1). Power must only be redistributed without SOC feedback control after the corresponding subsystem is full.…”
Section: Battery-charging Containermentioning
confidence: 99%
“…Thus, researchers are gradually focusing on clean and sustainable renewable energy [1]. However, areas with abundant renewable energy resources are dispersed in remote locations, where local energy consumption is low but longdistance transmission capacity is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The global electricity production from wind sources is estimated at about 300,000 MW for 2015 compared to the 60,000 MW in 2005 [2]. With the promulgation of the Renewable Energy Law in 2005 [3], the electricity production from renewable energy in China has grown rapidly [4]. Recently, it has been shown that wind power output is an intermittent energy resource [5].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, flexible network configuration and operation mode under distribution automation (DA) provide the great potential to improve operation efficiency and assets utilization resulting in less grid construction [4,5]; on the other hand, smart grid introduces large amounts of renewable distributed generations (DG) into the distribution systems. These DGs produce far less CO 2 than traditional thermal power, and may reduce power losses [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency and security is difficult to be balanced without proper management approach [4][5][6][7]. Although the problems aroused by DGs and electric vehicles have been studied in the research of Active Distribution Network (ADN) [8][9][10][11], on-line security assessment and control is rarely involved.…”
Section: Introductionmentioning
confidence: 99%